EFEKTIVITASMODEL KOOPERATIF TIPE GALERI BELAJAR UNTUK MENINGKATKAN KETERAMPILAN KEWARGANEGARAAN SISWA DALAM PEMBELAJARAN PKN : Studi Eksperimen Kuasi di Sekolah Menengah Kejuruan Teknologi Industri Pembangunan Cimahi - Insani, Nisrina Nurul (2017)
Kurangnyatanggungjawabpesertadidikdalammenyelesaikantugas, kurangnyainisiatifdankreatifitaspesertadidikdalammenghadapipermasalahan, danrendahnyakemampuanpemahamanmerupakanmasalah yang terjadiakibatrendahnyaketerampilankewarganegaraansiswa. Olehsebabitu, studiinibertujuanuntukmeningkatkanketerampilankewarganegaraansiswa. Rumusanmasalahdalamstudiiniadalah : "Apakah model pembelajarankooperatifgaleribelajarefektifmeningkatkanketerampilankewarganegaraansiswa?" Studieksperimenkuasiinimemilihkelas X SMK TeknologiIndustri Pembangunan Cimahisebagaipopulasi. Sampeldalamstudiiniantara lain siswakelas X TEI B (kelaseksperimen) yang menggunakan model pembelajarankooperatifgaleribelajardan X TEI C (kelaskontrol) yang menggunakan model pembelajarankooperatiftipepetakonsep. Hasilstudimenunjukkanbahwa rata-rata nilaiposttest 80.0000 kelaseksperimenlebihbesardaripadanilaipretest yaitu 60.8000. 92 persensiswa di kelaseksperimenmendapatkannilaiposttestnyalebihtinggidibandingkannilaipretest. BerdasarkanhasildariperhitunganWilcoxon Signed Rank Test, makanilai Z yang didapatsebesar -4.091 dengan p value (Asymp. Sig. 2 tailed) sebesar 0.000 dimanakurangdaribataskritispenelitian 0.05 sehinggakeputusannyahipotesisadalahmenerima H1atauberartiterdapatperbedaanbermaknaantarapretestdanposttest padakelaseksperimen. Hasilanalisisangketjugamenunjukkan 60 persensiswalebihmemilihselaluatauseringdalammenjawabpernyataan yang diberikanmengenaiketerampilankewarganegaraanDengandemikianhipotesis yang menyatakan model pembelajarankooperatifgaleribelajarefektifmeningkatkanketerampilankewarganegaraansiswadapatditerima. Kata kunci:model pembelajarankooperatif, galeribelajar, keterampilankewarganegaraan, The lack of students' responsibility in accomplishing task, lack of their initiative and creativity in facing the problem, and low of understanding ability is the problem occurred as a result of students' civic skill which is low. Therefore, this study is aimed to enhance students' civic skill. The formulation of problem in this study is : "Whether cooperative learning model of gallery walk is effective to in enhancing students' civic skill?" This quasi experimental study select class X of SMK TeknologiIndustri Pembangunan Cimahi as population of study. The sample of study are students of class X TEI B (experiment class) who use cooperative learning study of gallery walk and X TEI C (control class) who use cooperative learning model with mind mapping type. The result of study showed that mean of posttest score for experiment class is 80.0000 which is higher than pretest score which is 60.8000. 92 percent of students in experiment class obtain posttest score which is higher compared to pretest score. Based on Wilcoxon Signed Rank Test calculation, Z value obtained is -4.091 with p value (Asymp. Sig.2 tailed) is 0.000 which less than critical limit of study, that is, 0.05 so it is decided to accept hypothesis H1 or it means there is significant difference between pretest and posttest in experiment class. The result of questionnaire analysis also show that 60 percent of students more choose always or often in answering the statement given about civic skill. Hence, the hypothesis which state that cooperative learning model of gallery walk is effective in enhancing students' civic students can be accepted. Keywords: cooperative learning model, gallery walk, civic skill